Pengaruh Konsentrasi Sukrosa terhadap Karakteristik Minuman Probiotik Sari Buah Jambu Biji Merah dengan Isolat Lactobacillus sp. F213 - Tri Handayani, Ni Komang; Nocianitri, Komang Ayu; Suparthana, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
This research was aimed to determine the effect of sucrose concentration on the characteristics of red guava probiotic juice with Lactobacillus sp. F213 isolates and to determine the right concentration of sucrose that produced the best characteristics of red guava probiotic juice. This research used a completely randomized design with concentration of sucrose as treatments, which consisted of six levels: 0%, 2%, 4%, 6%, 8% and 10%. Each treatment was repeated 3 times to obtain 18 units of samples. The data of lactic acid bacteria total were analyzed descriptively and the data of total sugar, total acid, pH, sensory properties were analyzed by Analysis of Variance, and if the treatment affected the observed parameters significantly (P<0,05), it was continued with Duncan Multiple Range Test. The results showed that concentration of sucrose significantly affected to total sugar, total acid, pH, taste (hedonic), sour taste (score), sweet taste (score) and overall acceptance (hedonic), but no significant effect on color (hedonic) and aroma (hedonic). The 8% sucrose concentration produced the best red guava probiotic juice with the characteristics of total LAB 8,56 Log CFU/ ml, total sugar 10,60%, total acid 0,12%, pH 4,06, the color and the aroma were preferred, with slightly sour and sweet taste were preferred, and overall acceptance was preferred.